A distância mínima de códigos parametrizados no toro projetivo - Cunha, Grégory Duran (2014)
This work aims at presenting the parameters of codes parameterized on the algebraic projective torus. We also present a characterization for the torus using the concept of clutters. The tool that we use come from Groebner basis theory and algebraic geometry. The thesis contains a brief introduction to these concepts as well as the basic facts from nite eld theory and linear codes theory. We also present an optimal bound for the regularity of the ideal of a projective torus.